Clinical research Normalization of the Verbal Fluency Test on the basis of results for healthy subjects, patients with schizophrenia, patients with organic lesions of the chronic nervous system and patients with type 1 and 2 diabetes - Wysokiński, Adam; Zboralski, Krzysztof; Orzechowska, Agata; Gałecki, Piotr; Florkowski, Antoni; Talarowska, Monika (Archives of Medical Science, 2010)
Introduction: Verbal fluency is the ability to form and express words compatible with required criteria. Verbal fluency is necessary for optimal communication and for normal social and occupational functioning. The Verbal Fluency Test is a good indicator of frontal lobe dysfunction, particularly of the left frontal cortex. Material and methods: The aim of the study was to compare verbal fluency in healthy subjects (n = 50), patients with paranoid schizophrenia (n = 36), patients with organic lesions of the central nervous system (CNS) (n = 33), and patients with diabetes (n = 62) – type 1 diabetes (n = 31) and type 2 diabetes (n = 31). Results: Healthy subjects and patients with diabetes achieved the highest results in all categories of the Verbal Fluency Test. Patients with paranoid schizophrenia achieved significantly lower results. Sten norms of the Verbal Fluency Test were developed for the general population. Using these norms it was found that subjects with schizophrenia or with organic lesions of the CNS had very poor results more often and very high results less frequently compared to healthy subjects and also to patients with diabetes. Conclusions: This observation is consistent with the neurodevelopmental hypothesis of schizophrenia, in which cognitive functions of the frontal lobe (e.g. verbal fluency) play a major role in the psychopathological picture. We have also demonstrated that in patients with type 1 and 2 diabetes verbal fluency is comparable with healthy subjects.